HEYNEA TRIJUGA: POTENTIAL INSECTICIDAL & GROWTH AND DEVELOPMENT ACTIVITY AGAINST SPILARCTIA OBLIQUA (LEPIDOPTERA: ARCTIIDAE) (Acta Entomologica Serbica, 2022)
Plants are recognized as an important natural source of pesticides. They have a diverse range of chemicals to protect themselves against various pests/diseases. Extracts of the fruit pericarp of Heynea trijuga were evaluated for pesticidal and insect growth regulator (IGR) activity against Spilarctia obliqua under laboratory conditions. For three generations castor leaves treated with hexane and acetone extracts of Heynea trijuga (1-10%) were fed to 3rd instar larvae for five days and then untreated fresh leaves were given till pupation. An adverse morphogenic effect on various biological parameters (larval duration, pupal duration, adult emergence and fecundity) was observed in treated insects. The growth and development of insects were significantly affected in a dose-dependent manner. Larval duration, larval mortality, prepupal mortality, postpupal mortality and pupal duration increased with increase in concentration while, larval weight, adult emergence, fecundity and egg fertility decreased with increase in concentrations of extracts. The acetone extract showed better growth regulating activity than the hexane extract. The bioactive substances in H. trijuga extracts could be responsible for behavioral effects and post-ingestive toxicity and have good potential to be developed as insecticide/growth regulators.